Separation of styrene and ethylbenzene on metal-organic frameworks: analogous structures with different adsorption mechanisms - Maes, Michael; Vermoortele, Frederik; Alaerts, Luc; Couck, Sarah; Kirschhock, Christine E A; Denayer, Joeri F M; De Vos, Dirk E (Journal of the American Chemical Society, 2010)
The metal-organic frameworks MIL-47 (V(IV)O{O(2)C-C(6)H(4)-CO(2)}) and MIL-53(Al) (Al(III)(OH)·{O(2)C-C(6)H(4)-CO(2)}) are capable of separating ethylbenzene and styrene. Both materials adsorb up to 20-24 wt % of both compounds. Despite the fact that they have identical building schemes, the reason for preferential adsorption of styrene compared to ethylbenzene is very different for the two frameworks. For MIL-47, diffraction experiments reveal that styrene is packed inside the pores in a unique, pairwise fashion, resulting in separation factors as high as 4 in favor of styrene. These separation factors are independent of the total amount of adsorbate offered. This is due to co-adsorption of ethylbenzene in the space left available between the packed styrene pairs. The separation is of a non-enthalpic nature. On MIL-53, the origin of the preferential adsorption of styrene is related to differences in enthalpy of adsorption, which are based on different degrees of framework relaxation. The proposed adsorption mechanisms are in line with the influence of temperature on the separation factors derived from pulse chromatography: separation factors are independent of temperature for MIL-47 but vary with temperature for MIL-53. Finally, MIL-53 is also capable of removing typical impurities like o-xylene or toluene from styrene-ethylbenzene mixtures.